A systematic review of estimates of the minimal clinically important difference and patient acceptable symptom state of the Western Ontario and McMaster Universities Osteoarthritis Index in patients who underwent total hip and total knee replacement. Issue 10 (October 2019) - MacKay, C.; Clements, N.; Wong, R.; Davis, A.M.
Summary: Objective: To systematically review the minimal clinically important difference (MCID) and patient acceptable symptom state (PASS) estimates in pain and function measured using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) in patients who underwent primary total knee replacement (TKR) and primary total hip replacement (THR). Design: The study was carried out following PRISMA recommendations. We searched five electronic databases. Two reviewers independently screened titles, abstracts and full-text papers using a priori inclusion/exclusion criteria. Data were extracted by two independent reviewers. Data were synthesized, with WOMAC values converted to 0–100 scores (0 = best, 100 = worst). Results: Thirteen studies were included. Research methods used to calculate MCIDs and PASS varied across studies (e.g., using anchor-based or distribution methods, wording of anchor questions within anchor-based methods). Baseline WOMAC scores also varied across studies. Across studies and methods, MCIDs for the WOMAC in patients undergoing TKR ranged from 13.3 to 36.0 for pain and 1.8–33.0 for function; values for WOMAC in THR ranged from 8.3 to 41.0 for pain and from 9.7 to 34.0 for function. PASS cut-offs for TKR ranged from 25.0 to 28.6 for pain and 32.3–36.7 for function, and cut-offs for THR from 15.0 to 30.6 for pain and 28.0–42.0 for function. Conclusion: Although the WOMAC is a commonly used measure for a single condition, the variability in methods used to calculate MCID and PASS estimates results in a range of values across studies making it unclear whether values reported in the literature can be applied with confidence. Future research is needed to refine methods used to calculate MCIDs and PASS.